Symbolic Interaction of Director of Photography in Film Production Organizing at Camera Department - Utami, Citra Dewi; Arifianto, Budi Dwi (Universitas Muhammadiyah Yogyakarta, 2019)
Film production is a collaborative work process that involves many workers. Proper management is needed to achieve effective and efficient production results. Organizing is the second function of management work. The film production workers are divided into several departments, one of which is the camera department. In this department, all visual matters are accounted for. Director of Photography (DP) is the leader. Data collection in this research was carried out through archive studies, observations, and interviews. This article discusses how DP symbolically interacted in certain pattern with directors, producers, and crew in the camera department. The discussion uses the five concepts of Blumer's symbolic interaction, namely self-concept, the concept of action; object concept; the concept of social interaction; and the concept of joint action. The results of the discussion from this study indicate that the DP interacts with the director through productive self-appearances, has improved visual aesthetic achievements, and masters the latest equipment through works uploaded on social media. The action shown by the DP to the director as the boss is communicated using the concept language and his efforts to the camera department crew as subordinates are communicated using technical language. The DP interacts with the producer through a work contract; The DP interacts socially symbolically with the broader community through language selection that is adapted to the working environment. Finally, the DP interacts through collective action, working together with one department worker and between departments in a production process so that they can work together to produce a film.